2022
DOI: 10.7860/jcdr/2022/59062.17369
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function Status in Nephrotic Syndrome in Paediatric Age Group: A Hospital-based Cross-sectional Study

Abstract: Introduction: Nephrotic syndrome, being one of the common glomerular diseases in the paediatric population, is characterised by massive proteinuria and has a negative impact on thyroid function, necessitating investigation. Aim: To assess the status of thyroid function in nephrotic syndrome in the paediatric age group. Materials and Methods: This descriptive cross-sectional study was carried out at Bankura Sammilani Medical College and Hospital (BSMCH) in Bankura, West Bengal, India. The study included 100 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The prevalence was 41.16%, 62%, and 70.8% in a study done in Korean, Indian and Egyptian populations respectively. 1 , 6 , 8 A case-control study from Iran found elevated TSH levels in 34.2% of nephrotic children compared to controls (10.8%). 9 …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence was 41.16%, 62%, and 70.8% in a study done in Korean, Indian and Egyptian populations respectively. 1 , 6 , 8 A case-control study from Iran found elevated TSH levels in 34.2% of nephrotic children compared to controls (10.8%). 9 …”
Section: Discussionmentioning
confidence: 99%